Environmental disclosure quality and risk: the moderating effect of corporate governance. Issue 4 (10th June 2020) - Rezaee, Zabihollah; Alipour, Mohammad; Faraji, Omid; Ghanbari, Mehrdad; Jamshidinavid, Babak
Abstract : Purpose: The purpose of this article is to investigate the relationship between environmental disclosure quality (EDQ) and risk and to further examine whether corporate governance (CG) practices moderate this relationship. Design/methodology/approach: This study uses a set of unique, hand collected data (from 2011 to 2016) to measure EDQ for a sample of 762 firm-years Iranian listed companies. Ordinary least squares regression analysis is performed in testing hypotheses after controlling for a variety of firm, industry and year effects. Moreover, several analyses are performed to establish the robustness of the findings. Findings: The results indicate a negative association between EDQ and firm risk. While board independence moderates this relationship, other CG practices such as CEO duality and board size do not show any effects on the relationship between EDQ and risk. The results remain robust after performing sensitivity tests and under various specifications, including the fixed-effects panel data and Heckman two-stage regressions. Research limitations/implications: Results are from a sample of firms from one country. Practical implications: The results have implications for policymakers, legislators and corporate executives, as environmental initiatives are gaining more attention worldwide. Social implications: Sustainability initiatives in the areas of environmental and social performance and disclosure are gaining global attention. This study addresses the link between firm risk and EDQ. Originality/value: This study contributes to the literature by shedding light on the relationship between corporate risk-taking and EDQ in the context of a developing economy.